PENERAPAN PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK (PMR) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS II A SD NEGERI 25 PEKANBARU - Hanisah '; Drs. Hamizi '; Erlisnawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :The main problem of this research is that the result of learning mathematics for II A grade student of SD Negeri 25 Pekanbaru was too low about 61,06 out of standard 75. This could be happen because all this time students seldom finish the tasks given to them, and lack of enthusiasm on learning because the teacher still uses lecturing method and never gives motivation and reward for all the effort and the result of student’s learning. The purpose of this research is to increase the result of learning mathematics on II A grade student of SD Negeri 25Pekanbaru.The main question in this research is can application of approach learning realistic matematica education improve the result of studying mathematics of II A grade SD Negeri 25 Pekanbaru students?”. Subjects on this research involve the 33 fifth A students people which consist of 17 boys and 16 girls. Score was obtained from result of learning test in final exam cycle. The result of this research indicaded that 10 students passed the standars score (30,3%)in pretest and increased into 23 students(69,7%) in cycle I, 29 students (87,9%)in cycle II. From that data is can be coucluded that the application of approach learning realistic matematica education can increase the result of studying mathematica of II A grade students in SD Negeri 25 Pekanbaru.Key Words: approach learning.realistic mathematica education, achievement